Marine invertebrates and fishes exhibit inconsistent body size responses to ocean acidification - Mary E. Hart; Sean D. Connell; Angus Mitchell; Ben P. Harvey; Sylvain Agostini; Joshua M. Heitzman; Ivan Nagelkerken (Limnology and Oceanography, 2026)
Body size is a fundamental characteristic of all living organisms that determines physiological functions and life‐history traits. Ecological theory predicts that ocean acidification can cause body size reductions, confirmed by several studies reporting miniaturization in ectotherms. Based on this prediction, we would expect a broad suite of species to show similar plastic body‐size responses to elevated CO 2 . Using four natural climate change analogues of ocean acidification across the northern and southern hemispheres, we quantified body size alterations across 18 marine invertebrate and fish taxa to test for climate‐driven miniaturization. Only three species consistently showed body‐size reductions under ocean acidification: one urchin and two fish species. In contrast, 15 other species, ranging from highly calcified to non‐calcified, displayed unchanged or increased body sizes or inconsistent miniaturization. If body‐size miniaturization responses were consistently reproducible across taxa we would have observed it more frequently, suggesting that species responses to ocean acidification are more variable than previously thought and likely vary depending on a species' physiology and life history. Thus, rather than entire communities undergoing miniaturization, species are likely to display a spectrum of responses, with some exhibiting size reductions, others demonstrating physiological resistance to elevated CO 2 , and others potentially benefiting from the indirect effects of ocean acidification.